Comparative Performance of Four Established Neonatal Disease Scoring Systems in Predicting In-Hospital Mortality and the Potential Role of Thromboelastometry - Rozeta Sokou (MDPI AG, 2021)
Background: To compare the prognostic accuracy of the most commonly used indexes of mortality over time and evaluate the potential of adding thromboelastometry (ROTEM) results to these well-established clinical scores. Methods: The study population consisted of 473 consecutive term and preterm critically-ill neonates. On the first day of critical illness, modified Neonatal Multiple Organ Dysfunction (NEOMOD) scoring system, Score for Neonatal Acute Physiology (SNAP II), Perinatal extension of SNAP (SNAPPE), and SNAPPE II, were calculated and ROTEM standard extrinsically activated (EXTEM) assay was performed simultaneously. Time-to-event methodology for competing-risks was used to assess the performance of the aforementioned indexes in predicting in-hospital mortality over time. Time-dependent receiver operator characteristics curves for censored observation were compared across indexes. The addition of EXTEM parameters to each index was tested in terms of discrimination capacity. Results: The modified NEOMOD score performed similarly to SNAPPE. Both scores performed significantly better than SNAP II and SNAPPE II. Amplitude recorded at 10 min (A10) was the EXTEM parameter most strongly associated with mortality (A10 < 37 mm vs. ≥37 mm; sHR = 5.52; p < 0.001). Adding A10 to each index apparently increased the prognostic accuracy in the case of SNAP II and SNAPPE II. However, these increases did not reach statistical significance. Conclusion: Although the four existing indexes considered showed good to excellent prognostic capacity, modified NEOMOD and SNAPPE scores performed significantly better. Though larger studies are needed, adding A10 to well-established neonatal severity scores not including biomarkers of coagulopathy might improve their prediction of in-hospital mortality.